2020
DOI: 10.1016/j.futures.2020.102645
|View full text |Cite
|
Sign up to set email alerts
|

The six scenario archetypes framework: A systematic investigation of science fiction films set in the future

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…We followed grounded theory guidelines (Charmaz 2014; Strauss and Corbin 1998) and adapted the procedures of Fergnani and Song (2020a) with three steps of data coding and analysis: films transcriptions, coding, and emergent theory construction . This approach fits well with our goal of extracting theory from films, which is a novel methodological development in grounded theory (Fergnani and Song 2020a, 2020b).…”
Section: Methodsmentioning
confidence: 53%
See 1 more Smart Citation
“…We followed grounded theory guidelines (Charmaz 2014; Strauss and Corbin 1998) and adapted the procedures of Fergnani and Song (2020a) with three steps of data coding and analysis: films transcriptions, coding, and emergent theory construction . This approach fits well with our goal of extracting theory from films, which is a novel methodological development in grounded theory (Fergnani and Song 2020a, 2020b).…”
Section: Methodsmentioning
confidence: 53%
“…Futures scholars have paid attention to films, particularly sci-fi films, for their implications for Futures studies (Lombardo and Ramos 2015; Rumpala 2012). Fergnani and Song (2020b) studied the social imaginaries of the future through 140 films set in the future. They identified six major images portrayed in films, Growth & Decay, Threats & New Hopes, Wasteworlds , The Powers that Be, Disarray, and Inversion, which represent six macroscopic scenarios of destiny of humankind, that is, scenario archetypes.…”
Section: Theoretical Background: Collective Social Imaginaries and Filmsmentioning
confidence: 99%
“…CLA (Inayatullah, 1998) deconstructs the internal dimension of the future by looking at collective perceptions. Several scenario planning methods, most notably the intuitive logics tradition (Schwartz, 1996; van der Heijden, 1996; Chermack, 2011) and archetypal approaches (Bezold, 2009a, 2009b; Dator, 2009; Fergnani & Song, 2020; Hines & Bishop, 2020), are relativeley more focused on the external or operational environment. Identity Wind Tunneling can enhance both internally and externally focused scenario methods as it considers how perceptions of organizational identities, a distinctive internal dimension, can play out in several futures of the external environment.…”
Section: Discussionmentioning
confidence: 99%
“…Serra (2013) argued that incasting has to do with seeing “the future” from alternative perspectives, which is to say that this approach emphasizes the necessity of alternative views rather than focusing on organizational identity, although the process of articulating a preferred future requires at least the presumption of a well‐articulated organizational identity. How organizational identity is questioned is also left unexplored in subsequent adaptations and enhancements of Dator's archetypal approach (Bezold, 2009a, 2009b; Fergnani & Song, 2020; Hines & Bishop, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This set of archetypes clearly expands previous generic types of scenarios as suggested for instance by Jim Dator who distinguished essentially between four types: (1) Growth/Continuation, (2) Limits/Discipline, (3) Decline/Collapse and (4) Transformation (various publications). On the other hand, a study based on the analysis of 140 science fiction confirmed only three of these previously proposed archetypes and claims to have uncovered three new archetypes (Fergnani & Song, 2020). As a result of an online survey with 950 participants representative of the Australian population, they find a high degree of correspondence, but not a total match, between their six archetypes and five identified myths or attitudes towards the future 3 .…”
Section: Archetypes In Recent Scenario Studiesmentioning
confidence: 92%